Correlates of jail crowding in the United States - Wooldredge, John D. (American journal of criminal justice, 1989)
Jail populations across the United States have grown dramatically over the last decade. However, research on the correlates and causes of jail crowding is very rare. This study examined several structural, legal, demographic and socio-demographic correlates to the degree to which a jail’s average daily population was under or over the jail’s rated capacity during 1983. Results suggest that there might be a variety of contributing factors to jail crowding in the United States. These factors include a jurisdiction’s serious crime rate, available resources for incapacitation relative to the number of convicted criminal defendants, degree of urbanism, degree of political conservativism, degree of prison crowding in a state, types of jail standards and inspection intervals, and the type of jail facility.